2016
DOI: 10.1038/srep37828
|View full text |Cite
|
Sign up to set email alerts
|

Fine tuning of Rac1 and RhoA alters cuspal shapes by remolding the cellular geometry

Abstract: The anatomic and functional combinations of cusps and lophs (ridges) define the tooth shape of rodent molars, which distinguishes species. The species-specific cusp patterns result from the spatiotemporal induction of enamel knots (EKs), which require precisely controlled cellular behavior to control the epithelial invagination. Despite the well-defined roles of EK in cusp patterning, the determinants of the ultimate cuspal shapes and involvement of epithelial cellular geometry are unknown. Using two typical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 51 publications
(55 reference statements)
1
33
0
Order By: Relevance
“…Similarly, disruption of the main components of the cytoskeleton‐associated proteins has been found to contribute to the misshaping of the final cusp pattern in mammals . Also, the disturbance of fibronectin, E‐cadherin, or F‐actin distribution in lophodont gerbils has been previously described to contribute to ectopic invagination of inner enamel epithelium . Moreover, the expression of matriptase (ST14), which mediates assembly of adherent junctions, is lost in these epithelial cells, confirming specific changes in cell membranes during cluster cell formation.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Similarly, disruption of the main components of the cytoskeleton‐associated proteins has been found to contribute to the misshaping of the final cusp pattern in mammals . Also, the disturbance of fibronectin, E‐cadherin, or F‐actin distribution in lophodont gerbils has been previously described to contribute to ectopic invagination of inner enamel epithelium . Moreover, the expression of matriptase (ST14), which mediates assembly of adherent junctions, is lost in these epithelial cells, confirming specific changes in cell membranes during cluster cell formation.…”
Section: Discussionmentioning
confidence: 75%
“…This alteration of Na/K‐ATPase activity indicates modifications in membrane function as a possible developmental process responsible for the cell shape changes during enamel ridge formation. Similarly, disruption of the main components of the cytoskeleton‐associated proteins has been found to contribute to the misshaping of the final cusp pattern in mammals . Also, the disturbance of fibronectin, E‐cadherin, or F‐actin distribution in lophodont gerbils has been previously described to contribute to ectopic invagination of inner enamel epithelium .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…During tooth development, Twist1 is expressed in the mesenchyme, and mesenchymal-conditional Twist1-KO mice show an inhibition of odontoblast differentiation caused by the inhibition of epithelial-mesenchymal interactions (23). In Epfn-KO mice, the dental epithelial cells failed to polarize, and after the bell stage, the immature dental epithelium randomly invades into the mesenchymal region to form multiple teeth (7,9,31). In the present study, we demonstrated that the AmeloD expression in the invading dental epithelial cells of Epfn-KO teeth caused abnormal migration of epithelial cells through partial EMT processes (Fig.…”
Section: Discussionmentioning
confidence: 99%